2022
DOI: 10.3389/fpsyg.2022.802925
|View full text |Cite
|
Sign up to set email alerts
|

Older Women’s Loneliness and Depression Decreased by a Reminiscence Program in Times of COVID-19

Abstract: The confinement caused by the current COVID-19 pandemic protects physical health, but in turn, has a long-lasting and far-reaching negative psychosocial impact; anxiety, stress, fear and depressive symptoms. All of these have a particular impact on vulnerable older people, putting them at serious risk of loneliness. Women report feeling lonelier than men, affecting women to a greater extent. The present study aims to analyze the efficacy of an integrative reminiscence intervention in older women living in nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 86 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…One RCT conducted in 24 primary care clinics of Brazil that applied a 17‐week psychosocial program based on psychoeducation and behavioral activation approaches obtained positive results in reducing depression in older adults 146 . Another study conducted in Spain with a sample of 34 older women living in nursing homes (intervention group ( n = 14) and control group ( n = 20)), which applied a reminiscence program, demonstrated positive results of the intervention in reducing depressive symptoms and feelings of loneliness 147 . Moreover, studies with samples of adults of other ages have also shown positive results in reducing depressive symptoms, such as a study with a sample of students who used the Smartphone app MCT & More 148 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One RCT conducted in 24 primary care clinics of Brazil that applied a 17‐week psychosocial program based on psychoeducation and behavioral activation approaches obtained positive results in reducing depression in older adults 146 . Another study conducted in Spain with a sample of 34 older women living in nursing homes (intervention group ( n = 14) and control group ( n = 20)), which applied a reminiscence program, demonstrated positive results of the intervention in reducing depressive symptoms and feelings of loneliness 147 . Moreover, studies with samples of adults of other ages have also shown positive results in reducing depressive symptoms, such as a study with a sample of students who used the Smartphone app MCT & More 148 …”
Section: Discussionmentioning
confidence: 98%
“…146 Another study conducted in Spain with a sample of 34 older women living in nursing homes (intervention group (n = 14) and control group (n = 20)), which applied a reminiscence program, demonstrated positive results of the intervention in reducing depressive symptoms and feelings of loneliness. 147 Moreover, studies with samples of adults of other ages have also shown positive results in reducing depressive symptoms, such as a study with a sample of students who used the Smartphone app MCT & More. 148 Taken together, our findings demonstrate that it is possible to conduct interventions for depression, even with the constraints associated with the pandemic.…”
Section: Interventions Implemented To Decrease Depressive Symptomsmentioning
confidence: 99%
“…16 Preoccupation with a bitter past reflects an inability to fulfil 12 This finding has important clinical implications for helping older adults build meaningful interpersonal relationships with others, solidify their identities, and find meaning in their lives through reminiscence-based interventions. For example, through group reminiscence sessions, [41][42][43] they could freely discuss their memories, enhance social inclusion, identify and shift depressogenic thinking, and generate alternative ways of thinking about the past (cognitive reconstruction). Additionally, group reminiscence therapy provides a social environment that fosters connectedness and social interactions between individuals, improving social interactions and combating loneliness.…”
Section: Predicting Depression and Lonelinessmentioning
confidence: 99%